2020
DOI: 10.5146/tjpath.2020.01515
|View full text |Cite
|
Sign up to set email alerts
|

Giant igg4-related pseudotumor of the esophagus resected with endoscopic submucosal dissection: a case report and review of the literature

Abstract: IgG4-related disease (IgG4-RD) is a systemic autoimmune disorder that has been defined in various organs. The disease is characterized by typical clinicopathological features including a dense lymphoplasmacytic infiltrate rich in IgG4 positive plasma cells, storiform fibrosis, obliterative phlebitis, and often an elevated serum IgG4 level. Esophageal IgG4-RD is rare, and its presentation as a solid mass is even more rare. Only 15 previous cases of IgG4-related esophageal disease have been described. We herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The oesophageal involvement of IgG4-RD (IgG4-RDE) has been uncommonly reported in the literature. Nese et al [ 1 ] reported that only 15 cases in the literature have previously described the oesophageal involvement of IgG4-RDE. CMV-associated gastrointestinal diseases usually occur in immunocompromised patients; however, a few cases have also been described in healthy hosts [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oesophageal involvement of IgG4-RD (IgG4-RDE) has been uncommonly reported in the literature. Nese et al [ 1 ] reported that only 15 cases in the literature have previously described the oesophageal involvement of IgG4-RDE. CMV-associated gastrointestinal diseases usually occur in immunocompromised patients; however, a few cases have also been described in healthy hosts [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that IgG4-RDE is more frequent in males and occurs most often in elderly patients. The clinical symptoms of IgG4-RDE primarily include dysphagia and weight loss, and, more rarely, odynophagia, epigastric pain, and acid reflux [ 1 ]. Gastric endoscopies can reveal ulcerations and strictures, or mass-like lesions, mainly involving the distal and mid-oesophagus [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation